Effects of intestinal microbes on rheumatic diseases: A bibliometric analysis - Huang, Runzhi; Zhang, Mengyi; Lu, Yuwei; Xu, Dayuan; Liu, Yifan; Jin, Minghao; Xian, Shuyuan; Wang, Siqiao; Tong, Xirui; Lu, Jianyu; Zhang, Wei; Qian, Weijin; et al. (Frontiers in Microbiology, 2023)
Background: Rheumatic diseases are a group of multi-system inflammatory autoimmune diseases whose causes are still under study. In the past few decades, researchers have found traces of the association between rheumatism and intestinal microbiota, which can partially explain the pathogenesis of rheumatic diseases. We aimed to describe the research trend and main divisions on how gut flora interreacts with rheumatic diseases, and discussed about the possible clinical applications. Methods: We analyzed bibliometric data from the Web of Science core collection (dated May 15th, 2022). Biblioshiny R language software packages(bibliometrix) were used to obtain the annual publication and citations, core sources according to Bradford’s law, and country collaboration map. We designed and verified the keyword co-occurrence network and strategic diagram with the help of VOSviewer and CiteSpace, and we manually processed the tables of most local cited documents and core sources. Results: From a total of 541 documents, we found that the overall trend of annual publication and citation is increasing. The major research method is to compare the intestinal microbial composition of patients with certain rheumatic disease and that of the control group to determine microbial alterations related to the disease's occurrence and development. According to Bradford’s law, the core sources are Arthritis & Rheumatology, Annals of the Rheumatic Diseases, Current Opinion in Rheumatology, Nutrients, Rheumatology, and Journal of Rheumatology. Since 1976, 101 countries or regions have participated in studies of rheumatology and intestinal microbes. The United States ranks at the top and has the broadest academic association with other countries. Five themes were identified, including the pivotal role of inflammation caused by intestinal bacteria in the rheumatic pathogenesis, the close relationship between rheumatism and inflammatory bowel disease, immunoregulation mechanism as a mediator of the interaction between rheumatic diseases and gut flora, dysbiosis and decreased diversity in intestine of patients with rheumatism, and the influence of oral flora on rheumatic diseases. Conclusion: Studies on rheumatism and the intestinal microbiota are growing. Attention should be paid to the mechanism of their interaction, such as the microbe-immune-rheumatism crosstalk. Hopefully, the research achievements can be applied to diseases’ prevention, diagnosis, and treatment.